PENERAPAN METODE TALAQQI OLEH TPMQ (TIM PENJAMIN MUTU AL-QURAN) UNTUK MENINGKATKAN KUALITAS BACAAN AL-QURAN SISWA - Istiqomah, Rofiatul; Anam, Nurul; Rusydi, M; Yaqin, M. Ainul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The importance of knowing the Qur'an for human life is the driving force behind this study. Therefore, having facilities capable of printing generations of the Qur'an is very important for their development. In this case, Pondok Pesantren Al-Qodiri 1 Jember, one of the founding institutions of Jember, formed a special team called TPMQ (Al-Qur'an Quality Assurance Team) to supervise the recitation of the Qur'an by students. Based on the above background, the following problem formulation can be put forward, What is the TPMQ Strategy to Improve the Quality of Students' Al-Qur'an Reading? , How is the application of the Talaqqi Method at MTs Al-Qodiri Featured 1 Jember? , How well is the development of MTs students' reading skills?. This research uses a descriptive qualitative approach. The descriptive nature is categorized as field research. How to collect data through observation, documentation, and interviews. The research was conducted at MTs. The flagship of Al-Qodiri 1 Jember, which is one of the institutions run by the Al-Qodiri 1 Jember Islamic Boarding School Foundation. Based on the results of the research, learning the Qur'an with the talaqqi method used by TPMQ at MTs Unggulan Al-Qodiri 1 Jember is very effective and can improve students' Al-Qur'an reading skills.